2016
DOI: 10.3329/bjog.v27i1.29908
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hayman Suture Technique in the Management of Atonic Post-Partum Hemorrhage

Abstract: Objective: To study the effectiveness of Hayman suture technique to control postpartum hemorrhage.Method: Hayman suture was applied in 43 cases. A No-1 Vicryl suture was used on a round body or a straight needle. In 36 cases (83.72%) Hayman suture was the only intervention. In 4 cases (9.30%) uterine vessels and ovarian vessels were also ligated along with Hayman suture. In 3 cases (7%), along with Hayman suture, Gunashila’s circumferential sutures were taken. Results: None of the 43 patients required hysterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In a study done by Majumdar et al, (2012) succeeding to stop PPH using Hayman suture was sufficient in 83.7%, while requiring additional maneuver was in 7% of cases. Hysterectomy was avoided in all of the cases 100%.…”
Section: Demographic Datamentioning
confidence: 93%
See 1 more Smart Citation
“…In a study done by Majumdar et al, (2012) succeeding to stop PPH using Hayman suture was sufficient in 83.7%, while requiring additional maneuver was in 7% of cases. Hysterectomy was avoided in all of the cases 100%.…”
Section: Demographic Datamentioning
confidence: 93%
“…The other studies showed similar results to our study. Majumdar et al, (2012) reported an average blood loss of 1640 ml ±487 ml, and Fahmy et al, (2016) reported an average blood loss of 1450 ml± 500 ml. The blood loss with mean bleeding 1310.4 ± 730.3 mL was in the studies conducted by Moreno-santillán et al, (2018), andJosé et al, (2020) reported the average of quantified bleeding in the group was 1475.39 ± 716.82mL (range between 950 and 3250mL).…”
Section: Demographic Datamentioning
confidence: 99%